Controlling axillary intra‐aortic balloon pump inflation is a viable option for turning an acute heart failure patient into a chronic one. Issue 7 (20th February 2019) - Barac, Yaron D.; Schroder, Jacob N.; Bishawi, Muath; Patel, Chetan B.; Milano, Carmelo A.; Daneshmand, Mani A.
Abstract: Intra‐aortic balloon pump (IABP) is often used to support patients in decompensated heart failure. Placement of the IABP via the axillary artery facilitates long‐term support with the device and may allow for the conversion of an acute heart failure (HF) patient into a chronic HF patient using a modified weaning protocol; allowing for medical symptom management and removal of mechanical support. We will discuss strategies for supporting these complicated patients.